The Influence of Workload and Leadership Style on Employee Performance - Faradini Filiyan; Agustin Hari Prastyowati; Muhaimin Dimyati (Innovation Business Management and Accounting Journal, 2025)
This research is motivated by the problem of the performance of DPRD Secretariat employees which is considered less than optimal. The purpose of this study is to analyse the effect of workload and leadership style on organizational commitment and its impact on employee performance. The approach used is quantitative with the Structural Equation Modelling-Partial Least Square (SEM-PLS) method. The population of this study was all DPRD Secretariat employees, with a sample of 80 people taken through saturated sampling techniques. The results of the study indicate that workload has a significant effect on organizational commitment, indicating that good workload management can increase employee loyalty. In addition, leadership style also has a significant effect on organizational commitment, where an inspiring and supportive leadership style can strengthen employee engagement. Workload and leadership style have been shown to have a significant effect on performance, indicating that appropriate workload and effective leadership can increase employee productivity and work results. Organizational commitment also has a significant effect on performance, where employees with high commitment show greater dedication. In addition, organizational commitment mediates the effect of workload and leadership style on employee performance. This study emphasizes the importance of workload management, the application of appropriate leadership styles, and strengthening organizational commitment in efforts to improve the performance of DPRD Secretariat employees.